Effects of Caring Leadership in Nursing Services: Scoping Review - Roselien Putri Ariestianti; Luky Dwiantoro; Meidiana Dwidiyanti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Nurses have many complex problems when carrying out their nursing services affected high number of nursing turnover. The head nurse plays an important role in solving the problems faced by her staff. One of the leadership styles that can be used is caring leadership. The results of previous studies show that caring leadership has a positive impact to nurses. The purpose of this paper is to determine the effect of caring leadership carried out by the head nurse in nursing services. Method: The method used in this writing is scoping review. Literature search was taken from data based on Pubmed, Science Direct, Proquest, and EBSCO with restrictions on the year of publication 2019 – 2023. There are 2 outlines of the effects of caring leadership in nursing services including: direct effects on nursing service work and indirect effects. Caring leadership is one of the leadership styles that can be used by the head nurse. The results of this paper can be used as a consideration in nursing for the selection of leadership style to be used.